SUSPECTS: enabling fast and effective prioritization of positional candidates. - Adie, Euan A; Evans, K.; Porteous, David; Pickard, B.; Adams, Richard R (Oxford University Press, 2006)
SUSPECTS is a web-based server which combines annotation and sequence-based approaches to prioritize disease candidate genes in large regions of interest. It uses multiple lines of evidence to rank genes quickly and effectively while limiting the effect of annotation bias to significantly improve performance.